2018
DOI: 10.1016/j.bbamcr.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Control of nuclear β-dystroglycan content is crucial for the maintenance of nuclear envelope integrity and function

Abstract: β-Dystroglycan (β-DG) is a plasma membrane protein that has ability to target to the nuclear envelope (NE) to maintain nuclear architecture. Nevertheless, mechanisms controlling β-DG nuclear localization and the physiological consequences of a failure of trafficking are largely unknown. We show that β-DG has a nuclear export pathway in myoblasts that depends on the recognition of a nuclear export signal located in its transmembrane domain, by CRM1. Remarkably, NES mutations forced β-DG nuclear accumulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…In this study, we generated a C12C12 myoblasts-based model with no expression of DG (α-DG and β-DG) using CRISPR-Cas9 technology to provide insights into the nuclear function of β-DG. In earlier studies, we showed that β-DG is involved in maintaining the structure and function of the NE [ 20 , 21 ]; nevertheless, the specific mechanisms underlying its role in these nuclear processes remains to be determined. We isolated two DG-knockout clones (DG-KO1 and DG-KO2) that were generated from two different gRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we generated a C12C12 myoblasts-based model with no expression of DG (α-DG and β-DG) using CRISPR-Cas9 technology to provide insights into the nuclear function of β-DG. In earlier studies, we showed that β-DG is involved in maintaining the structure and function of the NE [ 20 , 21 ]; nevertheless, the specific mechanisms underlying its role in these nuclear processes remains to be determined. We isolated two DG-knockout clones (DG-KO1 and DG-KO2) that were generated from two different gRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that β-DG assembles with the nuclear envelope (NE) proteins emerin and lamins A/C and B1 to maintain nuclear architecture and function in myoblasts [ 20 ]. β-DG is subject to nucleocytoplasmic shuttling with an active exportin1/CRM1-mediated nuclear export pathway [ 21 ] that together with its nuclear import serves to tightly regulate the nuclear levels of β-DG, thereby allowing effective interactions with binding partners at the NE interface. However, the molecular basis underlying the role of β-DG on NE-associated functions is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of cell cycle was carried out on a BD LSRFortessa flow cytometer (BD Biosciences), using the ModFit LT software (Verity Software House). Cell proliferation was assessed by the 3‐(4,5‐dimethylthiazole‐2–5‐diphenyl tetrazolium bromide (MTT) assay, as reported previously (Velez‐Aguilera et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the functional diversity of the NE it is likely that new NE-located proteins must still be identified. Our recent studies revealed that β-DG is a previously unrecognized NE component, which is likely to be involved in the maintenance of nuclear structure and function, probably by serving as a scaffold for the assembly of a NE protein complex composed of emerin and lamins A/C and B1 [ 4 , 10 ]. Thus, characterization of the molecular interaction of β-DG with NE proteins would help to decipher its function in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Within the nucleus β-DG forms a complex with the NE proteins emerin and lamins A/C and B1, to preserve nuclear structure and function [ 4 , 10 ] and probably to regulate gene expression [ 11 ]. It is possible that nuclear trafficking of β-DG connects functionally the plasma membrane with the NE, via an as yet undefined mechanism, thus allowing the cell to orchestrate nuclear activity in response to external stimuli [ 8 ].…”
Section: Introductionmentioning
confidence: 99%